Adaptability of Cymodocea serrulata (R.Br.) Aschers. and Magnus to different environment - Lam, S.L (2015)
Cymodocea serrulata plants under different environments showed morphological plasticity. The short-stemmed (normal) plants are those found in open areas or unshaded by seaweeds or seagrasses. In shaded areas, turbid waters (high suspended loads, sedimentation) and unstable soft substrates C. serrulata adapted to such conditions by adjusting expansion of the vertical erect stem, leaf and leaf sheath lengths in order to get sufficient light. In turbid waters and an environments of great instability the response can also be from horizontal expansion achieved by having longer rhizome internodes. Bi-directional (vertical and horizontal) expansions in vegetative structures of C. serrulata are the acclimatization of the plants to environmental influences. These morpological plasticities allow the plants to have selective advantage in habitats with low light created by Sargassum spp. and E. acorodies, turbid water and in sub-tidal zone. Variation in leaf features such as the presence of red bands on leaves of C. serrulata was also observed. The variations described point to the role of specific habitat conditions on the morphological adaptability of C. serrulata.